Response of Some Biochemical and Mineral Constituents of the Postharvest Mango (Mangifera indica L.) Influenced by Different Levels of Bavistin DF - M. Khairul Islam; A. K.M. Rafiul Islam; M.A.R. Sarkar; K.A. Hakim; N. Alam (Graduate Program of Syiah Kuala University, 2013)
AbstractAn investigation was carried out with the postharvest mangoes (viz., the Langra and the Khirshapat) treating with different levels of Bavistin DF solution (namely, 250, 500, and 750 PPM) for obtaining results on the biochemical and mineral content changes as well as storability of postharvest mango. The results of the experiments exhibited that only the single effect of varieties was found to be significant in most of the parameters studied. The Langra enriched a greater quantity of crude fiber, lipid, water-soluble protein, phosphorus, and potassium constituents over the Khirshapat. It is revealed that the expansion of mineral contents in the mango was intimately associated with ripening during storage. The results also noticed to be an increasing trend of lipid and protein content in mango pulp with the advance of storage period using Bavistin DF. Keywords: Postharvest mango; Biochemical constituents; mineral contents; Bavistin DF.